Key factors that impact customer service delivery in South African retail banks. - Matlhole, Kenneth Paul (My University, 2016)
Purpose – To determine the service-quality factors that are important to South African retail banking customers. With the changes taking place within the economic environment like technology advancements and banking deregulation, competition is increasing in which servicing is being used as tool for competitive advantage. Design/methodology/approach – A total of 217 South African retail bank customers responded to a questionnaire, which was based on SERVQUAL. Confirmatory and Exploratory Factor Analysis (EFA) were used to validate the SERVQUAL Model, and to identify other relationships between the service constructs. Using the means from the importance scale, the service attributes were ranked. The Wilcoxon-Mann-Whitney and Kruskal Wallis test were applied to measure the statistical difference of means between the demographic groups of age, gender and income. Findings – Fit statistics indicated that the observed data was not a good fit to the SERVQUAL scale. High correlation was observed between the service dimensions. EFA produced four dimensions, namely credibility and accuracy, tangible representation, attitudes and behaviour and eService access. With regard to demographic impact, only low importance had a statistical difference of means. Research limitations/implications – There were some difficulties in obtaining a normal distribution of channel usage, ethnicity, and age distribution. Future research could be directed at how service importance is impacted by channel usage, ethnicity, and understanding how service differs in a business-tobusiness (B2B) environment. Practical implications – Findings of this study might help South African retail banks identify which elements of service quality are important to customers, enabling banks to create strategic competitive specifications to meet customer demands. iii Originality/value – This study assesses the SERVQUAL instrument on the basis of importance ranking and with the aim of identifying service attributes. How technology has played a role in these service attributes is also explored. Keywords Retail banks, SERVQUAL, services quality, South Africa, Factor analysis
MBA
Keywords: Retail banks,SERVQUAL, services quality,factor analysis-----South Africa